Combined VEGF gene transfer and erythropoietin in ovine reperfused myocardial infarction - Olea, Fernanda Daniela (2013)
BACKGROUND: In reperfused acute myocardial infarction (RAMI), cardioprotective treatments may enhance myocardial salvage and hence reduce the area of necrosis. Based on studies showing that plasmid-mediated vascular endothelial growth factor (pVEGF) gene transfer reduces infarct size by combining angio-arteriogenic and cardiomyogenic effects and that erythropoietin (EPO) exerts anti-apoptotic actions in animal models of AMI, we aimed to assess if their association would reduce infarct size to a larger extent than any of them individually in a large mammalian model of RAMI. METHODS: Adult sheep subjected to 90-minute coronary artery occlusion received upon reperfusion intramyocardial pVEGF 3.8 mg plus intravenous EPO 1000 IU/kg (n=8), pVEGF (n=8), EPO (n=8) or placebo (n=8). RESULTS: Fifteen days after treatment, infarct size was smaller in the 3 treatment groups (pVEGF+EPO: 8 ± 1 %; pVEGF: 16 ± 5 %; EPO: 13 ± 4 %) compared to placebo (25 ± 7 %, p<0.001). However, in the EPO+VEGF group infarct size was significantly smaller than in the groups receiving EPO or VEGF individually (p<0.05). DNA fragmentation, a hallmark of late apoptosis, was significantly lower in sheep receiving EPO. The combined treatment, while not affecting global left ventricular performance, improved regional peri-infarct function and prevented over-time expansion of the post-infarct perfusion defect. CONCLUSIONS: Combined pVEGF and EPO treatment might be clinically useful to enhance the benefits of early revascularization in patients with acute myocardial infarction.